2022
DOI: 10.1371/journal.pgph.0001321
|View full text |Cite
|
Sign up to set email alerts
|

The supply is there. So why can’t pregnant and breastfeeding women in rural India get the COVID-19 vaccine?

Abstract: Despite COVID-19 vaccines being available to pregnant women in India since summer 2021, little is known about vaccine uptake among this high need population. We conducted mixed methods research with pregnant and recently delivered rural women in northern India, consisting of 300 phone surveys and 15 in-depth interviews, in November 2021. Only about a third of respondents were vaccinated, however, about half of unvaccinated respondents reported that they would get vaccinated now if they could. Fears of harm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…We found negative significant correlation between vaccination rates and pregnancy rates (between the ages of 15 and 19 years) and percentages of children exclusively breastfed. Women of childbearing age were eligible for vaccination during the fourth phase of vaccination, but a lack of scientific evidence and clear communication surrounding potential side-effects of the vaccine on a pregnant or a breastfeeding woman might have driven this finding [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found negative significant correlation between vaccination rates and pregnancy rates (between the ages of 15 and 19 years) and percentages of children exclusively breastfed. Women of childbearing age were eligible for vaccination during the fourth phase of vaccination, but a lack of scientific evidence and clear communication surrounding potential side-effects of the vaccine on a pregnant or a breastfeeding woman might have driven this finding [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health education dissemination strateg innovation is critical to meet the scope and depth required for population-level coverage, particularly for novel threats. Our team’s formative research identified vaccine misinformation related to pregnant and breastfeeding women, but confirmed high vaccine interest and need for tools to negotiate with other household decision-makers 24. Additionally, we found that women were in need of trusted information sources 24…”
Section: Introductionmentioning
confidence: 54%
“…Main vaccination barriers for pregnant and postpartum women included fear of adverse effects (48.3%) and unsure of safety (25.1%) 23. Our formative research found low vaccination despite high healthcare provider access for antenatal care; half of unvaccinated women wanted to receive COVID-19 vaccination now (47%), 20% soon and 27% not at all 24. Safety concerns were reported more frequently by unvaccinated participants 24.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…During phase 4, districts that had higher pregnancy rates between the age of 15 and 19 years and higher percentage of children exclusively breastfed had lower vaccination rates. Women of child bearing age were eligible for vaccination during the fourth phase of vaccination, but lack of scientific evidence and clear communication surrounding potential side-effects of the vaccine on a pregnant or a breastfeeding woman could have driven this finding [65,66,67].…”
Section: Resultsmentioning
confidence: 99%